STUDENTS’ COGNITIVE EMOTION REGULATION IN ENGLISH ONLINE LEARNING PROCESS - Indriyani Astuti (Teaching English and Language Learning English Journal, 2022)
Abstract. The main goal of this research was to find out the students’ cognitive emotion regulation in English online learning process at English Education Program of Muhammadiyah University of Bengkulu. Qualitative design was applied in this study. The data from respondents were collected through an interview adapted from Gamefski, 2010). The result of this research revealed that the students applied all of the nine cognitive emotion regulations. Self-Blame, Catastrophizing, Acceptance, and Rumination were the most commonly used out of the nine strategies. It was concluded that there were variations on the students’ cognitive emotion regulation in English online learning process. Key words: Cognitive Emotion Regulation, English Online Learning